Coffee culture, destinations and tourism - Jolliffe, Lee (Tourism and cultural change., 2010)
"This book explores the various aspects of coffee culture around the globe, relating the rich history of this beverage and the surroundings where it is produced and consumed to coffee destination development and to the visitor experience. Coffee and tourism venues explored range from the cafe districts of Australia, Canada, Germany and New Zealand to the traditional and touristic coffee houses of Malaysia and Cyprus to coffee-producing destinations in Africa, Asia, Latin America and the Pacific."--Jacket.